Policing cross-border fraud ‘Above and below the surface’: mapping actions and developing a more effective global response - Button, Mark (Crime, law and social change, 2025)
Cross-border fraud, including its various forms such as online retail fraud, pyramid schemes, romance fraud and pig butchering, is a major problem around the world. Despite clear evidence that cross-border fraud is growing, there is little research charting the scale of cross-border fraud and the optimal policing responses to deal with it. This paper aims to fill this research gap by exploring what we know about the nature of cross-border fraud and current policing response. Unlike in other crime areas with a cross-border element, international bodies and nation states have shown very little interest in addressing cross-border frauds through what we term the higher profile ‘above the surface’ activities. Instead, policing responses have been present on a much larger scale in the private sector ‘below the surface’, with much less profile. Moreover, the paper argues that while cooperation and coordination between the public and private sector actors is crucial, there are very few policing structures bringing these diverse actors together to tackle cross-border fraud, among other gaps. By drawing on examples of alternative structures dealing with cross-border economic crime, the paper informs policy-makers by mapping out key actions and structures which should be considered to better tackle the global problem of cross-border fraud.